Combined threats to native smooth-shelled mussels (genus Mytilus) in Australia: bioinvasions and hybridization. Issue 4 (7th September 2021) - Zbawicka, Małgorzata; Wenne, Roman; Dias, Patricia Joana; Gardner, Jonathan P A
Abstract: Human-mediated pressures, including bioinvasions, threaten the biotas of every continent. Hybridization and introgression between invasive and native species may result in loss of genetic integrity of native taxa but, in many cases, these events are hard to detect because the invader is impossible to tell apart from the native taxon. The problem of cryptic invasive taxa and its importance for biodiversity protection have been underestimated, because of the limited number of studies of broadly distributed taxa using sensitive nuclear DNA markers. We employed a panel of 51 single nucleotide polymorphism (SNP) markers to examine genetic interactions between Australian native smooth-shelled mussels, Mytilus planulatus, and invasive and cryptic Northern Hemisphere M. galloprovincialis along 4400 km of coastline from the Pacific to the Indian Ocean. Overall, 20.8% of mussels from ten sites were native species. The centre of distribution of M. planulatus is in south-eastern Australia, in particular in Tasmania. We suggest that ongoing spatial and temporal monitoring of Tasmanian sites is required to test for the presence of M. galloprovincialis and its possible further spread, and that hatchery production of M. planulatus for farming and reseeding into the wild may help reduce the likelihood of its loss.